Pembelajaran PJOK Materi Pencak Silat Kelas VII di SMP Negeri Se-Kecamatan Grabag Kabupaten Purworejo - Zain, Nazilatul Azizah; Setiawan, Ipang (Universitas Negeri Semarang, 2023)
This study aims to determine the description of learning physical education, physical sports and health of class VII pencak silat materials at State Junior High Schools in Grabag Sub-district, Purworejo Regency. This research uses descriptive quantitative research. The sampling technique used was purposive sampling. The instrument used in this research is a questionnaire with a measurement scale of 4 alternative answers with validity and reliability tests. Data analysis in this research is using quantitative descriptive analysis. . The results of this study showed that the teacher respondents showed the learning process of PJOK for Pencak Silat material in Class VII SMPN in Purworejo District in general, the teachers thought that the category tended to be low, with 45% giving low answers, while 33% answered moderate. Only 11% each answered very high and high Based on the results of the study, it was concluded that the learning of PJOK for class VII pencak silat material at State Junior High Schools in Grabag Sub-district, Purworejo Regency from aspects, among others, (1) planning for learning PJOK for pencak silat material was less than optimal (2) the implementation of learning tended to be in the low category, with a percentage of 44% of the answers. , and students show a percentage in the medium category with 46% (3) evaluation of learning PJOK material for pencak silat is classified as moderate.